Does access to an information‐based, breast cancer specific website help to reduce distress in young women with breast cancer? Results from a randomised trial. (23rd August 2018) - White, Victoria; Farrelly, Ashley; Pitcher, Meron; Hill, David
Abstract: To assess the effectiveness of a purpose‐built information‐based website to reduce distress among young women with breast cancer. A total of 337 participants (Intervention Group [IG] n  = 202; Usual Care Group [UCG] n  = 177) returned the completed baseline questionnaires (T1). Details regarding accessing the website were provided to IG participants. Follow‐up questionnaires were completed: (a) 3 months (T2) and (b) 6 months after baseline (T3). Outcomes included anxiety and depression (primary outcomes), quality of life (QoL) and unmet information needs. About 70% of the IG accessed the website, typically only once (median: 1, range 1–15), spending a median of 19 min (range: 1–315) on the site. Mean levels of anxiety and depression did not differ between the two groups at T1, T2 or T3. While improvement in total QoL was greater in the IG than UCG between T1 and T2, QoL scores did not differ between groups at T3. The number of unmet needs did not differ between the two groups at T3. The intervention was not effective in reducing anxiety, or depression in this group of women. As a high number of unmet needs were identified, other strategies for addressing these needs of young women with breast cancer are needed.